2015
DOI: 10.1155/2015/909514
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilusSuppresses Colitis-Associated Activation of the IL-23/Th17 Axis

Abstract: The aim of this paper is to determine the modulatory effects of Lactobacillus acidophilus on the IL-23/Th17 immune axis in experimental colitis. DSS-induced mouse models of UC were to be saline, hormones, and different concentrations of Lactobacillus acidophilus intervention. The expression of interleukin- (IL-) 17, tumor necrosis factor α (TNFα), IL-23, transforming growth factor β1 (TGFβ1), signal transducer and activator of transcription 3 (STAT3), and phosphorylated (p)-STAT3 was examined by RT-PCR, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 34 publications
4
79
1
2
Order By: Relevance
“…Additionally, the study showed that IL‐17‐driven inflammatory reaction led to bacterial clearance . None of the examined LAB strains induced this cytokine in our experimental system confirming that commensal LAB strains are rather poor IL‐17 inducers . Enhancement of Th1 response by Lr (low Treg population, low level of IL‐10, and high concentrations of IL‐12p70 and IFN‐γ) may promote the elimination of potentially pathogenic bacteria, such as Hp .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Additionally, the study showed that IL‐17‐driven inflammatory reaction led to bacterial clearance . None of the examined LAB strains induced this cytokine in our experimental system confirming that commensal LAB strains are rather poor IL‐17 inducers . Enhancement of Th1 response by Lr (low Treg population, low level of IL‐10, and high concentrations of IL‐12p70 and IFN‐γ) may promote the elimination of potentially pathogenic bacteria, such as Hp .…”
Section: Discussionsupporting
confidence: 55%
“…48 None of the examined LAB strains induced this cytokine in our experimental system confirming that commensal LAB strains are rather poor IL-17 inducers. 63,64 Enhancement of Th1 response by Lr (low Treg population, low level of IL-10, and high concentrations of IL-12p70 and IFN-γ) may promote the elimination of potentially pathogenic bacteria, such as Hp. 55 This is important because Hp counts in the individuals with symptomatic inflammation were shown to be higher than in the asymptomatic carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous probiotics have been found to downregulate IL-17 production and alleviate colitis, including B. breve (317), B. longum (318), L. acidophilus (319), B. longum subsp. infantis (304), and Streptococcus thermophilus ST28 (320).…”
Section: Protective Mechanisms Of Probiotics Against Ulcerative Colitismentioning
confidence: 99%
“…[3][4][5] Evidence for the role of the gut microbiome in psoriasis has been suggested by Zakostelska et al, 6 who have shown that exposure of mice to antibiotics inhibited psoriasis induction. The mice were characterized by an increase in fecal Lactobacilles, which suppress the interleukin-23-T-helper 17 axis, 7 implicated in psoriatic disease pathogenesis. 8 Others have shown that neonatal treatment of mice with vancomycin and polymyxin led to dysregulation of the gut and skin microbiota in adulthood, as manifested by exacerbated imiquimod-induced psoriasis.…”
Section: Introductionmentioning
confidence: 99%